Single base pair mutation analysis by PNA directed PCR clamping. - Orum, H (1993)
A novel method that allows direct analysis of single base mutation by the polymerase chain reaction (PCR) is described. The method utilizes the finding that PNAs (peptide nucleic acids) recognize and bind to their complementary nucleic acid sequences with higher thermal stability and specificity than the corresponding deoxyribooligonucleotides and that they cannot function as primers for DNA polymerases. We show that a PNA/DNA complex can effectively block the formation of a PCR product when the PNA is targeted against one of the PCR primer sites. Furthermore, we demonstrate that this blockage allows selective amplification/suppression of target sequences that differ by only one base pair. Finally we show that PNAs can be designed in such a way that blockage can be accomplished when the PNA target sequence is located between the PCR primers.